Catalisadores à base de Ni/(CeZr)O2/MgAl2O4 e Ni/(X2O3+ZrO2)/MgAl2O4 (X=La, Sm e Y) aplicados à tri-reforma do metano visando produção de hidrogênio e gás de síntese - Lino, Ananda Vallezi Paladino (Universidade Federal de São Carlos, 2019)
The Methane Tri-Reforming (MTR) is a combination of Methane Dry Reforming (MDR) and Methane Steam Reforming (MSR) coupled with the Partial Oxidation of Methane (POM). In the present work, nickel catalysts supported on MgAl2O4 spinel and the effect of the zirconia and zirconia associated to Ce, La, Sm and Y incorporation to this supported were evaluated on the MTR. The MgAl2O4 was prepared by Pluronic P123® assisted coprecipitation, which resulted in an increment in the specific surface area and pore volume. Zirconium oxide and the elements associated were incorporated in the spinel structure by the incipient impregnation technique. The concentration of such additives in the support was estimated considering the monolayer coverage on the MgAl2O4 surface. The Ni was also incorporated by incipient impregnation technique in a nominal concentration of 10% wt. The fresh catalysts were characterized using ex situ proceedings like XRD with Rietveld Refinement, N2 adsorption to determine textural properties, H2-TPR, H2-TPD, CO2-TPD, and in situ characterizations like XPD (X-ray Powder Diffraction) and XANES (X-ray Absorption Near Edge Structure). The catalysts were evaluated in MTR at 750oC. The catalysts which featured the lowest amounts of carbon deposited during reaction at 750oC were also evaluated at 650oC, aiming to verify the temperature effect on the catalytic performance. Among all the catalysts, the Ce-Zr catalyst increased the metallic dispersion, which allowed the decrease of the carbon deposition compared to non-promoted catalyst. Despite the catalyst with Zr supported on the MgAl2O4 had shown the lowest coke deposition, the incorporation of Zr associated to Ce led to highest products yields, H2 and CO, 68% and 63%, respectively. Thus, it was also studied the effect of varying the Ce/Zr molar ratio in the catalysts supports, with molar ratios of Ce/Zr= 1, Ce/Zr= 4 and Zr/Ce=0. They were characterized and evaluated in MTR at 750oC. Operational studies were executed using the catalysts with the Ce/Zr = 4, changing the spatial velocity (GHSV) and the feed composition. This catalyst was selected for such studies once its basicity was mainly from basic sites up to moderate strength, which contribute to minimize the coke deposition. Once the conversions increased as the spatial velocity diminished, the feed composition studies (effect of O2/CO2 and H2O/CO2 ratios) were evaluated using the GHSV= 2.95 mol.g 1.h 1. The O2/CO2 = 0.17 was considered more adequate, once the CO2 conversion was kept at around 60%, while the H2/CO ratio was close to 1.75. Increasing the O2/CO2 ratio from 0 to 1.5, the coke deposition decreased about 30 times, while varying the H2O/CO2 ratio from 0 to 1.4 decreased the carbon content about 8 times. Thus, the air increment in the feed stream contributed more effectively to diminish the carbon production than the H2O addition. The scanning electron microscopy and Raman spectroscopy, used to characterize the coke produced along the reactions showed that the carbon seems as filamentous, presenting a small graphitization degree, which demonstrates that it can be gasified under the reaction conditions.
Catalysts based on Ni/(CeZr)O2/MgAl2O4 and Ni/(X2O3+ZrO2)/MgAl2O4 (X=La, Y, Sm) applied to methane tri-reforming to production of hydrogen and synthesis gas
Keywords: Reforma do metano; Gás de síntese; Hidrogênio; Aluminato de magnésio; Methane reforming; Synthesis gas; Hydrogen; Magnesium aluminate; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA